Lightweighting cost impacts on market adoption and GHG emissions in U.S. light-duty vehicle fleet - Fan Yang; Aaron Brooker; Sarah Kleinbaum; David Gotthold (Environmental Research Communications, 2024)
Vehicle lightweighting is a promising strategy that can reduce energy consumption and GHG emissions without compromising vehicle’s performance or size. The cost of lightweighting plays a critical role in determining the adoption of lightweighting technologies by consumers and manufacturers among advanced vehicle technologies. This analysis estimates the cost of lightweighting needed to achieve significant light-duty vehicle adoption to provide reductions in use-phase GHG emissions. Three different costs of lightweighting scenarios in the U.S. market including a baseline scenario, advanced technology scenario, and widespread scenario are evaluated employing Automotive Deployment Options Projection Tool (ADOPT) in conjunction with other technology improvement assumptions (e.g., advancements in fuel and battery technologies, and material price reductions) from DOE. ADOPT leverages a database of over 700 existing vehicle models and options, enabling it to provide a high degree of realism and capture the unique characteristics of popular vehicles and the endogenously evolvement of the vehicle options. For baseline scenario, the use-phase GHG emissions are reduced by more than 50% and lightweighting fraction reaches 15% by 2046 compared to 2015 levels. The widespread scenario further reduces the GHG emissions by about 4% from the additional 10% glider mass reduction compared to the baseline scenario. The benefit came largely from lightweighting being implemented in the large market segment of lower-price vehicles, due to the relatively low lightweighting cost ($5/kg).